Crosstalk Among circRNA/lncRNA, miRNA, and mRNA in Osteoarthritis - Kong, Hui; Sun, Ming-Li; Zhang, Xin-An; Wang, Xue-Qiang (Frontiers in Cell and Developmental Biology, 2021)
Osteoarthritis (OA) is a joint disease that is pervasive in life, and the incidence and mortality of OA are increasing, causing many adverse effects on people’s life. Therefore, it is very vital to identify new biomarkers and therapeutic targets in the clinical diagnosis and treatment of OA. ncRNA is a nonprotein-coding RNA that does not translate into proteins but participates in protein translation. At the RNA level, it can perform biological functions. Many studies have found that miRNA, lncRNA, and circRNA are closely related to the course of OA and play important regulatory roles in transcription, post-transcription, and post-translation, which can be used as biological targets for the prevention, diagnosis, and treatment of OA. In this review, we summarized and described the various roles of different types of miRNA, lncRNA, and circRNA in OA, the roles of different lncRNA/circRNA-miRNA-mRNA axis in OA, and the possible prospects of these ncRNAs in clinical application.